High cGAS-STING expression associates with improved efficacy of neoadjuvant chemo-immunotherapy in head and neck squamous cell carcinoma - Wang, Miao; Shi, Menglin; Ding, Yiming; Zhang, Zishanbai; Ge, Yuze; Li, Zhixin; Jing, Yixin; Hu, Honglian; Chen, Xiaohong (Frontiers in Oncology, 2025)
PurposeNeoadjuvant chemo-immunotherapy (NACI) has demonstrated significant clinical advantages in head and neck squamous cell carcinomas (HNSCC), while clinical responses vary in different patients. This study investigated the correlation between the cyclic GMP-AMP synthase (cGAS, CGAS) and the stimulator of interferon genes (STING, STING1) expressions and the efficacy of NACI in HNSCC.MethodsThe correlation between CGAS and STING1 expressions and chemotherapy/immunotherapy drug sensitivity was analyzed using the GDSC and TCIA dataset. The study enrolled 38 HNSCC patients receiving NACI, with protein expressions of cGAS and STING evaluated via immunohistochemistry. The T cell abundance and tumor-T cell interactions in different CGAS and STING1 expression groups were analyzed using bulk RNA-seq and scRNA-seq data from open databases.ResultsThe mRNA expressions of CGAS and STING1 were negatively correlated with the IC50 of docetaxel and positively correlated with the efficacy of anti-PD-1 treatment (p<0.05). In the real-world cohort, cGAS and STING expressions were both positively related to NACI efficacy (p<0.05). The mRNA expressions of CGAS and STING1 were positively correlated with the abundance of Act-CD4 (CGAS: rho=0.416, p<2.21e-16; STING1: rho=0.26, p=1.82e-09), Act-CD8 (CGAS: rho=0.089, p=0.0425; STING1: rho=0.303, p=1.98e-12), NKT cell (CGAS: rho=0.255, p=0.3.78e-09; STING1: rho=0.375, p=2.2e-6). Tumor cells with increased expression of CGAS or STING1 showed enhanced interactions with T cells.ConclusionThis study confirms the positive correlation between cGAS and STING expressions and NACI efficacy, suggesting their role in immune activation and potential as biomarkers for predicting NACI efficacy in HNSCC.